Begonia fritschiana (Begoniaceae, Begonia section Baryandra), a new species from Quezon, Bukidnon, Philippines - Amoroso, Victor B.; Lamparas, Rica Joy V.; Lagunday, Noel E.; Dapar, Mark Llyod G.; Rubite, Rosario R. (Phytotaxa, 2023)
Begonia fritschiana from Mindanao Island is described as a new species endemic to the Philippines. This is the latest addition to the species-rich Begonia section Baryandra. It resembles Begonia caramoanensis but is distinguished by the consistent obliquely ovate leaves with shorter petioles, lamina glaucous abaxially and with marginal hairs, mostly solitary to singly-branched inflorescences with shorter white-glandular hairs on the pedicels and peduncle, one of the outer tepals pink, and glabrous ovary and ovary wings. Begonia fritschiana is known only from the type locality with one population and less than 100 individuals. The area is not currently protected under the country’s National Integrated Protected Areas System by the Department of Environment and Natural Resources. Because of ongoing threats such as illegal logging, poaching, and over collection of biological resources, the single area of occurrence with estimated extent < 10 km2, and the small number of < 100 individuals, we recommend a classification of B. fritschiana as Critically Endangered.